PUBLIC PERCEPTION OF THE VEHICLE OWNERSHIP TRANSFER FEES (BBNKB) INCREMENT POLICY IN BANDAR LAMPUNG - Nairobi Nairobi (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
The aim of the study is to estimate the number of vehicles with Lampung outside police numbers operating in Lampung and to find out the public perceptions of the Lampung Provincial Government's policy through Local Regulations Number 2 of 2011, regarding the increase in vehicle ownership transfer fees (BBNKB) from 10 percent to 12.5 percent, along with willingness to pay from the policy. This research applies survey method in Bandar Lampung city with the population of the people who are the owner of new motor vehicles including the four-wheeled and two-wheeled which were purchased starting in 2012 outside the province of Lampung. The sampling method used is cluster sampling, meaning that the population is divided into several clusters. As the population of vehicles which have no BE police number operating in Lampung is unknown, then the number of the sample is set to 100 respondents.Based on the result of the survey, it is unravelled that there are 18 percent of cars which have non-BE plate number operating in Lampung, and for motorcycles, there are only 4 percent. Another finding shows the fact that respondents buy vehicles outside the province of Lampung because the price difference is quite significant and they do not do second BNKB in Lampung Province in accordance with its operational area. From the willingnes to pay, all respondents approve that if the rate of BBNKB decreases back to 10 percent, most of them will return to buy a new vehicle in Lampung due to the fact that there will be smaller price difference between the price of a new car purchased in Lampung Province and new car purchased outside Lampung Province. BBNKB tariff reduction will provide opportunities for trade of vehicles in Lampung Province to be more competitive, thus, they can develop better. Moreover, there will be more exciting investments and more job fields in the automotive sector.JEL Classification: H20, H21, H24Keywords: BBNKB Tariff, Public Perception, Willingness to Pay